Quantification of ex vivo Neutrophil Extracellular Traps - Koji Tanaka; Masato Okigami; Yuji Toiyama; Yoshinaga Okugawa; Yasuhiro Inoue; Toshimitsu Araki; Yasuhiko Mohri; Akira Mizoguchi; Masato Kusunoki (Bio-Protocol, 2015)
Neutrophil extracellular traps (NETs) are fibrous mesh-like, web-like, or string-like structures which are composed of DNA, histones, and granule proteins such as neutrophil elastase or myeloperoxidase. When activated by phorbol myristate acetate, interleukin-8, lipopolysaccharide (LPS), and various pathogens, neutrophils release NETs. We reported that NETs were classified as two distinct forms; cell-free NETs that were released away from neutrophils and anchored NETs that were anchored to neutrophils. In general, extracellular DNAs are used as a surrogate marker of NETs. Here, we describe a protocol regarding quantitative procedures of extracellular DNAs released from ex vivo neutrophils activated by LPS using fluorometric double-stranded DNA (dsDNA) quantification assay.